PENGARUH PUPUK ZA DAN KOMPOS TERHADAP KANDUNGAN Pb, Zn, Cu DAN N TANAH SERTA HASIL TANAMAN PADA SISTEM BUDIDAYA BAWANG MERAH DI TEPI DANAU BATUR, KINTAMANI, BANGLI - Santosa, Shinta Lestari; Rai, I Nyoman; Diara, Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2020)
Vegetable cultivation is livelihoods for side Lake Batur communities, Kintamani, Bangli. Hilly natural conditions with a soil texture influenced by the eruption of Mount Batur, 900 m above sea level, and 900-3500 mm high rainfall, causing this region is very suitable for the cultivation of various vegetables, including shallot. One effort to meet the high demand for shallots is that efforts are made to improve cultivation techniques, including fertilizing to improve yields. In modern agriculture, the use of fertilizer is absolutely essential to trigger the level of crop production. The aims is to analyze the combination effect of using of inorganic fertilizer (ZA fertilizer) and organic fertilizer (compost fertilizer) on shallot vegetable cultivation systems on the content of pollutants, N nutrients and onion crop yields on the shores of Lake Batur, Kintamani District, Bangli Regency. The study using RBD with two factors where factor I: provision of organic fertilizer is leaf compost made aerobically (O), consisted of 3 levels, namely: O 0 = 0*, O 1 = 5* and O 2 = 10*and factor II: the application of inorganic fertilizer namely ZA (S) fertilizer, consisted of 3 levels, namely: S 0 = 0**, S 1 = 50** and S 2   = 100**, each repeated 3 times. The parameters observed were the growth and yield of shallots as well as the content of Pb, Zn, Cu and N nutrients in the soil. The nutrient content (N) in the soil, when using chemical fertilizer ZA and compost organic is not significantly different, as well as the results of onion plants, while the content of Pb, Zn and Cu on the use of chemical fertilizer ZA and organic compost, very real different. The highest soil Pb content in S 2 O 1 treatment is 30.07***, the highest soil Zn content in the S 2 O 1 treatment was 28.24***, and the highest soil Cu content in the S 1 O 2 treatment is 17.22***. *= tons/ha **= kg/ha ***= mg/kg Keywords: compost; contents Pb; Zn; Cu of soil; shallot; ZA.